Prevalence and Deficiency of Vitamin D among Children in Gharyan City: A Descriptive Study - Amal Abdussalam A. Hmaid; Amani Abdussalam A. Hmaid; Abdulmutalib Mohammed Alarbi; Hana Dhaw A. Awn; Aya Nooreddin Nassr; Haadil Jumaa M. Idaab (African Journal of Advanced Pure and Applied Sciences, 2024)
Vitamin D deficiency is a prevalent health issue among children, with potential consequences for bone health and overall well-being. This study aimed to investigate the prevalence of vitamin D deficiency in a pediatric population and identify associated factors. A cross-sectional study was conducted on 400 children (aged 1-10 years) recruited from medical laboratories in Gharyan City, Libya, between January 2022 and June 2024. Participants were categorized based on their vitamin D levels (deficient, insufficient, adequate, or optimal). Demographic data (age, gender) and vitamin D levels were collected and analyzed using descriptive statistics and two-way ANOVA. Approximately half of the study participants (49.75%) exhibited vitamin D deficiency. Females had a slightly higher prevalence of deficiency (27.5%) compared to males (22.25%). Significant differences in vitamin D levels were observed across age groups. Infants under 12 months had higher levels compared to older children (36-72 months). While gender was not a significant predictor of vitamin D deficiency in our study, previous research has suggested potential gender-related disparities. The findings of this study highlight the concerning prevalence of vitamin D deficiency among children in the region. Age appears to be a significant factor influencing vitamin D status, with younger children being more susceptible to deficiency. While gender may not be a major determinant in this population. The high prevalence of vitamin D deficiency in our study underscores the importance of promoting sun exposure, dietary intake of vitamin D-rich foods, and supplementation strategies to address this public health issue. Further research is needed to explore the underlying factors contributing to vitamin D deficiency in children